Poor oral health is associated with an increased risk of esophageal squamous cell carcinoma ‐ a population‐based case‐control study in China - Chen, Xingdong; Yuan, Ziyu; Lu, Ming; Zhang, Yuechan; Jin, Li; Ye, Weimin (International journal of cancer, 2017)
To further examine the association between oral hygiene and esophageal squamous cell carcinoma (ESCC) risk and the effect modification of other exposures, we conducted a population‐based case‐control study between 2010 and 2012 in Taixing, China, a high‐risk area for ESCC. Cases were primarily recruited from endoscopy units at local hospitals, supplemented by linkage to the local Cancer Registry. Control subjects were frequency matched to cases by sex and age (5‐year groups) and were randomly selected from the Taixing Population Registry. For the current analysis, data from 616 histopathologically confirmed cases and 770 controls with complete information on oral hygiene were analyzed. Unconditional logistic regression models, including oral hygiene indicators and potential behavioral confounders, were used to derive odds ratios (ORs) and 95% confidence intervals (CIs). Tooth loss was only marginally significantly associated with ESCC risk (yes vs. no, OR = 1.29, 95% CI 0.94–1.74). However, the excess risk increased with increasing numbers of lost teeth (more than 6 teeth lost vs. none, OR = 1.48, 95% CI 1.04–2.11). Tooth brushing once or less per day, compared with tooth brushing twice or more per day, was associated with a 1.81‐fold increased risk of ESCC. In the stratification analyses, the increased risks associated with these indicators of oral health were more pronounced in older subjects (age ≥ 70 years), women, non‐smokers, and non‐drinkers. Further studies are warranted to verify these findings and to explore the underlying mechanisms, e.g., changed oral microbiota, associated with poor oral hygiene. What's new? Little is known about the etiology of esophageal squamous‐cell carcinoma (ESCC) in regions with a high incidence of this cancer. Alcohol and smoking don't seem to fully explain it. In this study, the authors found that poor oral health was associated with a higher incidence of ESCC in the Taixing region of China. Better oral hygiene and more frequent tooth brushing were associated with decreased risk. These results may have important public‐health implications for preventing ESCC in high‐risk regions such as China, India, and some parts of Africa.